Modelling the Inhibitory Effect of SiO2-coated Zero-valent Iron/palladium Bimetallic Nanoparticles (Sio2-nZVI/Pd) Reductant on Pseudomonas putida as the Biocatalyst for 2,2â€™,4,4â€™-tetrabromodiphenyl ether Degradation (Journal of Environmental Microbiology and Toxicology, 2020)
The used of linearization technique using natural logarithm transformation, though standard, is erroneous and can just give an estimated value for the sole parameter measured; the specific growth rate. in this paper, for the first time we model the effect of nZVI/Pd and SiO2-nZVI/Pd nanoparticles on the growth of P. putida in MSM medium as modelled using models such as von Bertalanffy, Baranyi-Roberts, modified Schnute, modified Richards, modified Gompertz, modified logistics and the most recent Huang. The results show that the lag phases of P. putida cell at 4 h (0.5 g L-1 of SiO2-nZVI/Pd), 7.655 h (1.0 g L-1 of SiO2-nZVI/Pd), 11.76 h (0.5 g L-1 of nZVI/Pd) and 22.03 h (1.0 g L-1 of nZVI/Pd) respectively, which were longer than that of control, indicating the nanoparticles prolonged the exponential phase of cell growth. Moreover, in comparing the maximum growth ymax, which was 1.23x109, there was a decrease in the P. putida growth, i.e 1.20x109 (0.5 g L-1 of SiO2-nZVI/Pd), 1.06x109 (1.0 g L-1 of SiO2-nZVI/Pd), 1.04x109 (0.5 g L-1 of nZVI/Pd) and 8.59x108 (1.0 g L-1 of nZVI/Pd) respectively, with more decrease in growth at the P. putida growth with nZVI/Pd than SiO2-nZVI/Pd. On the other hand, when comparing the Âµmax, the control has a value of 0.08 while 0.073, 0.073, 0.089 and 0.86 are values at bacterial concentration of (0.5 g L-1 of SiO2-nZVI/Pd), (1.0 g L-1 of SiO2-nZVI/Pd), (0.5 g L-1 of nZVI/Pd) and (1.0 g L-1 of nZVI/Pd) respectively, indicating the specific growth rate decreases with both 0.5 g L-1 of SiO2-nZVI/Pd and 1.0 g L-1 of SiO2-nZVI/Pd and increases with 0.5 g L-1 of nZVI/Pd and 1.0 g L-1 of nZVI/Pd. It is clear from the results that coating of SiO2 on nZVI/Pd might drastically decrease the toxicity to P. putida cells.
Keywords: SiO2-coated Bimetallic Nanoparticles, P. putida, Growth, Mathematical model, Buchanan-3-phase